Optimization of conditions to achieve high content of gamma amino butyric acid in germinated black rice, and changes in bioactivities - Chkaiyavat Chaiyasut (2018)
© 2017, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved. The present study estimated the optimum germination conditions to achieve high content of Gamma-amino butyric acid (GABA) and other phytochemicals in Thai black rice cultivar Kum Payao (BR). The Box–Behnken design of response surface methodology was employed to optimize the germination conditions. The changes in the GABA, phytochemical content, impact of salt, and temperature stress variation on phytochemical content, and stability of GABA were studied. The results showed that 12 h of soaking at pH 7, followed by 36 h of germination was the optimum condition to achieve maximum GABA content (0.2029 mg/g of germinated BR (GBR)). The temperature (8 and 30 °C), and salt (50-200 mM NaCl) content affected the phytochemicals of GBR, especially GABA, and anthocyanins. Obviously, the antioxidant capability, and enzyme (α-amylase and α-glucosidase) inhibiting nature of BR was significantly (P < 0.001) increased after germination. The storage of GBR at 4 °C significantly, preserved the GABA content (∼80%) for 45 days. Primarily, the current study revealed the changes in phytochemical content, and bioactivity of Thai black rice cr. Kum Payao during germination. More studies should be carried out on pharmacological benefits of GABA-rich GBR.